2002
DOI: 10.1111/j.1654-109x.2002.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Are invaders disturbance‐limited? Conservation of mountain grasslands in Central Argentina

Abstract: . Extensive areas in the mountain grasslands of central Argentina are heavily invaded by alien species from Europe. A decrease in biodiversity and a loss of palatable species is also observed. The invasibility of the tall‐grass mountain grassland community was investigated in an experiment of factorial design. Six alien species which are widely distributed in the region were sown in plots where soil disturbance, above‐ground biomass removal by cutting and burning were used as treatments. Alien species did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 28 publications
2
16
0
2
Order By: Relevance
“…Bull thistle and other shade intolerant weedy species may not persist for long in these treated areas as overstory canopy cover increases within the treated areas. Decreases in non‐native abundance with time have been noted in other studies (Meiners et al 2002; Petryna et al 2002). Whether the proliferation of non‐native species is only an ephemeral concern or if their presence and persistence will influence ecosystem function over the long term is not well understood and warrants longer‐term studies of vegetation responses to fuel treatments.…”
Section: Discussionsupporting
confidence: 79%
“…Bull thistle and other shade intolerant weedy species may not persist for long in these treated areas as overstory canopy cover increases within the treated areas. Decreases in non‐native abundance with time have been noted in other studies (Meiners et al 2002; Petryna et al 2002). Whether the proliferation of non‐native species is only an ephemeral concern or if their presence and persistence will influence ecosystem function over the long term is not well understood and warrants longer‐term studies of vegetation responses to fuel treatments.…”
Section: Discussionsupporting
confidence: 79%
“…However, this pattern was not seen in the majority of the disturbance treatments where species richness did not differ from the controls. Terrestrial grassland studies linking disturbance to invasion success have reported a similar pattern (Petryna et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…Investigations of grassland taxa have found that disturbance was necessary for the establishment of non-indigenous grasses (Petryna et al, 2002;Burke and Grime, 1996;Hobbs and Huenneke, 1992). Experimental manipulation demonstrated that interactions between multiple types of disturbance such as grazing, soil disturbance and eutrophication, were found to have an increased effect on invader success (Burke and Grime, 1996;Hobbs and Huenneke, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For example, establishment of Centaurea diffusa, one of the most problematic introduced plant species in western North America, was shown to be enhanced by high resource availability, and both the densities and size of C. diffusa increased when competition was also reduced by partially removing resident grass vegetation (Seastedt and Suding 2007). Similarly, Petryna et al (2002) observed that the establishment and persistence of six plant species, including Cirsium vulgare and Oenothera erythrosepala that were introduced from Europe and have become abundant in the mountain grasslands in central Argentina, strongly depended on soil disturbances and aboveground biomass removal by cutting and burning.…”
Section: Introductionmentioning
confidence: 99%